Entrepreneurship Curriculum in Higher Education - Saputra, Yori Andes; Hernawan, Asep Herry; Dewi, Laksmi (Westscience Press, 2024)
This article explores the dynamic landscape of entrepreneurship education in higher education, focusing on the context of Industry 4.0 and the emergence of Society 5.0. Emphasizing the collaboration between people and technology, this research investigates how universities, particularly in Indonesia, are responding to the need for entrepreneurial skills among students. A descriptive research method with a Secondary Data Analysis (SDA) approach, this research studies existing literature and journals to provide a comprehensive understanding of entrepreneurship curriculum development. The results highlight the diverse definitions of curriculum and entrepreneurship, leading to a discussion of the foundations and principles that underpin effective entrepreneurship curriculum design. In conclusion, the critical role of entrepreneurship in preparing students for the ever-evolving job market, fostering creativity, innovation and essential entrepreneurial skills.